2011
DOI: 10.1007/s12558-010-0112-2
|View full text |Cite
|
Sign up to set email alerts
|

Building infrastructure for cancer research in Africa

Abstract: Cancer incidence in Africa is increasing as a result of aging populations, lifestyle changes, and improved detection. However, cancer etiology, prevention, and control in Africa are poorly understood, and survival rates from cancer are among the lowest in the world. Poor cancer survival suggests that improvements in health care, patient education, and relevant research are critically needed. An increase in research infrastructure is required to achieve adequate screening, diagnosis, and treatment of cancer in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…All experts surveyed in this study agreed with Ford et al, 49 who identified the most commonly reported barriers to participation in trials as socioeconomic status, ethnic minority status, cultural background, literacy level, lack of education about clinical trials, comorbidities, costs of trial participation, and inadequate or absent infrastructure. 50 The reluctance of governments and populations in Africa to participate in trials could be the result of historical transgressions and ethical ambiguities of colonial research and treatment campaigns while marginalizing African therapeutics and traditional healing. 51 These many challenges may seem insurmountable to the creation of a complex and locally responsive research agenda, but there are many encouraging developments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All experts surveyed in this study agreed with Ford et al, 49 who identified the most commonly reported barriers to participation in trials as socioeconomic status, ethnic minority status, cultural background, literacy level, lack of education about clinical trials, comorbidities, costs of trial participation, and inadequate or absent infrastructure. 50 The reluctance of governments and populations in Africa to participate in trials could be the result of historical transgressions and ethical ambiguities of colonial research and treatment campaigns while marginalizing African therapeutics and traditional healing. 51 These many challenges may seem insurmountable to the creation of a complex and locally responsive research agenda, but there are many encouraging developments.…”
Section: Discussionmentioning
confidence: 99%
“…Africa innately lends itself to the development of unique expertise in nutrition, palliative care, translational oncology, and socioeconomic barriers to care. 6 , 50 Patients often present in advanced stages with low overall survival. Therefore, palliative care research should be a priority.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, new research partnerships between HICs and other institutions with smaller patient populations are often hindered by a lack of expertise or may have competing priorities or inadequate infrastructure for high-quality cancer research. 34 35 Therefore, the result is a system in which an exclusive group of institutions receive a disproportionate number of resources and opportunities, perpetuating inequity.…”
Section: Where In Africa Is Cancer Research Done?mentioning
confidence: 99%
“…17 Additionally, collateral patient-level benefits can include increased personal care attention, greater focus paid to therapeutic dosages and their timings, and increased screening tests to determine eligibility and evaluations to determine outcomes, possibly resulting in improved clinical outcomes. 18 In Africa, examples of network development are found in the fields of cancer and epidemiology 19,20 but less so in palliative care, with notable country-level exceptions in South Africa and Uganda.…”
Section: Introductionmentioning
confidence: 99%